Does functional cup orientation change at minimum of 10 years after primary total hip arthroplasty? - Cotter, Brendan D.; Innmann, Moritz Maximilian; Dobransky, Johanna S.; Merle, Christian; Beaulé, Paul E.; Grammatopoulos, George (The journal of arthroplasty, 2020)
Background - Cup orientation has been shown to influence the postoperative risk of impingement and dislocation following total hip arthroplasty (THA) and may change over time due to changes in pelvic tilt that occur with aging. The purpose of this study is to determine if there is a significant change in acetabular cup inclination and anteversion over a 10-year period following THA. - Methods - A retrospective, multisurgeon, single-center cohort study was conducted of 46 patients that underwent THA between 1995 and 2002. A total of 46 patients were included, with a median age at surgery of 56 years, and a median time between initial postoperative radiograph and the most recent one being 13.5 years (minimum 10 years). Cup orientation was measured from postoperative and follow-up supine anterior-posterior pelvic radiographs. Using a validated software, inclination and anteversion were calculated at each interval and the change in cup anteversion and inclination angle was determined. Furthermore, the difference in the sacro-femoral-pubic angle was measured, reflecting the difference in pelvic tilt between intervals. - Results - No significant difference was detected between measurements taken from initial postoperative radiograph and measurements a minimum of 10 years later (P > .45), with the median (interquartile range) change in anteversion, inclination, and sacro-femoral-pubic being 0° (−1° to 3°), 1° (−3° to 2°), and 0° (−2° to 3°), respectively. - Conclusion - Our study found no significant change in functional cup orientation a minimum of 10 years after THA. No shifts in functional cup orientation as a result of altering spinopelvic alignment seemed to be present over a 10-year period.
Gesehen am 14.09.2020